2008
DOI: 10.1007/bf03160941
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen-induced nephrotoxicity: Pathophysiology, clinical manifestations, and management

Abstract: Acetaminophen-induced liver necrosis has been studied extensively, but the extrahepatic manifestations of acetaminophen toxicity are currently not described well in the literature. Renal insufficiency occurs in approximately 1-2% of patients with acetaminophen overdose. The pathophysiology of renal toxicity in acetaminophen poisoning has been attributed to cytochrome P-450 mixed function oxidase isoenzymes present in the kidney, although other mechanisms have been elucidated, including the role of prostaglandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
230
2
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(248 citation statements)
references
References 22 publications
6
230
2
10
Order By: Relevance
“…1). Tissue injuries other than in the liver have also been reported in acetaminophen overdose (27). Several miRNA species that are predominantly expressed in the brain, heart, lung, and spleen, based on our 6-tissue survey, were also observed at higher levels in acetaminophen-overdosed plasma samples.…”
Section: Changes In the Spectrum And Level Of Mirna In Liver And Plassupporting
confidence: 59%
“…1). Tissue injuries other than in the liver have also been reported in acetaminophen overdose (27). Several miRNA species that are predominantly expressed in the brain, heart, lung, and spleen, based on our 6-tissue survey, were also observed at higher levels in acetaminophen-overdosed plasma samples.…”
Section: Changes In the Spectrum And Level Of Mirna In Liver And Plassupporting
confidence: 59%
“…The best characterized of these disorders is hepatic toxicity produced by an acute acetaminophen overdose (1)(2)(3). Acute acetaminophen poisoning can also produce renal injuries that reduce glomerular filtration and cause renal tubule damage characterized by potassium and/or phosphate wasting (4)(5)(6)(7). The pathogenic mechanisms responsible for these acute renal disorders may parallel those responsible for hepatic injury but they are less well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, important findings obtained from case reports revealed that most cases of nephrotoxicity were diagnosed between 2 and 5 days after PCM overdose ingestion, 20 with a peak S. creatinine to occur at the 1 st week. In the present study, lack of nephrotoxicity, noted after 9 days of PCM treatment cannot definitely rule out late appearance of nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%